DETERMINATIONS OF THE SOWING TIME OF GRASS PEA IN TEF- GRASS PEA RELAY INTERCROPPING SYSTEMS - Agegnehu Shibabaw; Bitwoded Derebe; Yechale Mengie; Oumer Beshir; Wudu Getahun; Alemayehu Assefa (Agricultura)
Sowing of grass pea immediately after tef harvests as double-cropping is a popular agricultural practice in Vertisols of northwestern Amhara of Ethiopia. However, the productivity of grass pea in the tef-grass pea double cropping system is extremely unreliable due to the shortening of the growing period as a result of climate change. Tef-grass pea relay intercropping has practiced without a defined planting date for grass peas after tef sowing. Therefore, a field experiment was initiated to optimize appropriate sowing date of grass pea for tef- grass pea relay inter cropping systems during 2022 and 2023 main rainy seasons. The treatments contain five sowing dates of grass pea after tef sowing, namely: 35, 50, 65, 80, and 95 days after tef planting, and two contrasting tef verities Viz. Quncho and Tsedey in a factorial combination of a randomized complete block design with three replications. Sole tef, sole grass pea, and farmers practice (grass pea after tef harvested) were included as a check. Plant height, grain yield, and biomass yield were collected and subjected to analysis of variance using the SAS system. The highest grain yield of tef (1388 kg ha-1) and grass pea (1731 kg ha-1), land equivalent ration value (1.79), monitory advantage index (71890 Ethiopian birr) were obtained from planting of grass pea 80 days after Quncho  tef sowing. Therefore, planting of grass pea 80 days after Quncho tef sowing appeared to be the most appropriate sowing time to be recommended in Vertisols of Bahir Dar Zuria and North Achefer.